2010
DOI: 10.1093/toxsci/kfq085
|View full text |Cite
|
Sign up to set email alerts
|

Chloramphenicol Causes Mitochondrial Stress, Decreases ATP Biosynthesis, Induces Matrix Metalloproteinase-13 Expression, and Solid-Tumor Cell Invasion

Abstract: Overuse and abuse of antibiotics can increase the risk of cancer. Chloramphenicol can inhibit both bacterial and mitochondrial protein synthesis, causing mitochondrial stress and decreased ATP biosynthesis. Chloramphenicol can accelerate cancer progression; however, the underlying mechanisms of chloramphenicol in carcinogenesis and cancer progression are still unclear. We found that chloramphenicol can induce matrix metalloproteinase (MMP)-13 expression and increase MMP-13 protein in conditioned medium, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…Our experiments confirmed that lower concentrations of chloramphenicol (25 μg/mL) significantly inhibit primary MM cell proliferation, which is consistent with a previous report of inhibition of mouse myeloma cell proliferation by chloramphenicol [31]. Because chloramphenicol is highly fat soluble [11], it likely reaches higher concentrations in the bone marrow, where MM cells mainly survive and accumulate, than in the serum [32]. Thus, higher local drug concentrations may inhibit the growth of MM cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our experiments confirmed that lower concentrations of chloramphenicol (25 μg/mL) significantly inhibit primary MM cell proliferation, which is consistent with a previous report of inhibition of mouse myeloma cell proliferation by chloramphenicol [31]. Because chloramphenicol is highly fat soluble [11], it likely reaches higher concentrations in the bone marrow, where MM cells mainly survive and accumulate, than in the serum [32]. Thus, higher local drug concentrations may inhibit the growth of MM cells.…”
Section: Discussionsupporting
confidence: 92%
“…This inhibition of energy metabolism would change tumor biology, making it unconducive to tumor cell growth [8]. In contrast to previous reports [10, 11], a small increase in the chloramphenicol dose (to ≥ 50 μg/mL) greatly suppressed tumor growth while further decreasing ATP levels. These phenomena suggest that a deep deficiency in ATP can effectively suppress tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Exogenous drug resistance cassettes conferring chloramphenicol (cat), ␤-lactam (bla), and blasticidin (Shble) resistance are currently used as markers to select transformed Chlamydia (18,19,27,28). However, the bla cassette cannot be used in urogenital strains; chloramphenicol can cause mitochondrial stress (54), limiting its use during continuous passaging; and blasticidin S exhibits antibiotic activity toward both prokaryotic and eukaryotic cells and thus can be toxic to host cells. In addition, not all Chlamydiae species are susceptible to these antibiotics, such as Parachlamydia acanthamoeba, which is naturally resistant to ␤-lactams (55).…”
Section: Selection With Antibioticsmentioning
confidence: 99%
“…Abuse of chloramphenicol stimulates tumor development. This drug works through the JNK and PI3k pathways, which lead to a phosphorylated c-Jun protein binding to the promoter region of the matrix metalloproteinase-13 region (MM-13) [65]. The increased levels of the MM-13 protein lead to tumor development [66].…”
Section: Discussionmentioning
confidence: 99%